Persepsi dan preferensi masyarakat terhadap taman rekreasi bantaran Sungai Loloan Sanur - Pradipta, I Gede Angga; Sarwadana, Sang Made; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018, 2018)
Public Perception and Preference of Loloan Riverbank Recreational Park Sanur. Denpasar is a developing city. Like other developing cities in Indonesia, Denpasar City continues to carry out development in various aspects, one of which is the construction of a recreational park. Servers as a recreational facility and social interaction for the people of Denpasar City. One of the recreational parks being promoted is Recreational Park of Loloan Riverbanks located in Sanur Village. To maximize functionality and improve quality of The Recreational Park Loloan Riverbanks, therefore should be done research on this Recreational Park Loloan Riverbanks to know how perception and preference the community as a user of recreational park. This research used survey method with data collection techniques is observation, interview and questionnaire wich amounted to 30 copies for 30 respondent. Result of people’s perceptions showed Recreational Park of Loloan Riverbanks serves as a cheap recreational place and a cheap sport venue for the people’s of Denpasar City. Result of people’s preference showed addition of recreational park support facilities will lead to increased levels of enjoyment and visitor satisfaction from the Recreational Park of Loloan Riverbank. Public perception and preference of The Recreational Park Loloan Riverbanks used as information and references to the manager or related parties that play a role in managing The Recreational Park Loloan Riverbanks Denpasar City, so that later The Recreational Park Loloan Riverbanks will be liked by the community of Denpasar City.